PROGNOSTIC MODELS FOR CHRONIC LYMPHOCYTIC LEUKEMIA (CLL): A TEN-YEAR SYSTEMATIC REVIEW - Sijabat, Landong; Novettiandari, Guinanti (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: CLL is the most common malignant neoplasm of aging adults in Western populations. CLL is a hematology malignancy defined by the continuous proliferation of monoclonal B lymphocytes in bone marrow, peripheral blood, and lymphoid organs that have a specific immunophenotype. Clinical outcomes for patients with CLL are heterogeneous, leading to the development of prognostic factors. CLL-IPI is a commonly used tool for predicting outcomes. The aim: This study aims to determine the prognostic models for CLL. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SAGEPUB, and ScienceDirect, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Results: In the PubMed database, the results of our search brought up 27 articles, whereas the results of our search on SAGEPUB brought up 415 articles, our search on ScienceDirect brought up 742 articles. In the end, we included four research that met the criteria. Conclusion: In conclusion, of the five models, the CLL-IPI shows the best predictive performances. However, further research is needed.